Environmental Concerns Associated with the Development of the Agro-Industrial Complex and Analysis of Its Financing - LUKPANOVA, Zhanar; JUMABEKOVA, Almagul; MUKUSHEV, Abzal; MATAIBAYEVA, Gulnar; KADRINOV, Maulet; BAIMAGAMBETOVA, Zamzagul (Journal of Environmental Management and Tourism; Vol 13 No 5 (2022): JEMT, Volume XIII, Issue 5(61), Fall 2022DO - 10.14505/jemt.v13.5(61).15, 2022)
The world's agriculture is transforming from a traditional to a high-tech industry that is able to create new markets for innovative and investment decisions and developments, striving to increase labor productivity and yields. Only advanced mechanized solutions can sometimes help to achieve significant results in this area, given the current problems, as well as the economic, environmental and social challenges facing the countryside. The purpose of the study is to identify the environmental concerns associated with the development of the agro-industrial complex and the analysis of its financing in the Republic of Kazakhstan, as well as the creation of an environmentally oriented system for the utilization of agricultural waste.